Scientific Data Analysis using Jython Scripting and Java - Chekanov, Sergei V.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Scientific Data Analysis using Jython Scripting and Java presents practical approaches for data analysis using Java scripting based on Jython, a Java implementation of the Python language. The chapters essentially cover all aspects of data analysis, from arrays and histograms to clustering analysis, curve fitting, metadata and neural networks. A comprehensive coverage of data visualisation tools implemented in Java is also included. Written by the primary developer of the jHepWork data-analysis framework, the book provides a reliable and complete reference source laying the foundation for data-analysis applications using Java scripting. More than 250 code snippets (of around 10-20 lines each) written in Jython and Java, plus several real-life examples help the reader develop a genuine feeling for data analysis techniques and their programming implementation. This is the first data-analysis and data-mining book which is completely based on the Jython language, and opens doors to scripting using a fully multi-platform and multi-threaded approach. Graduate students and researchers will benefit from the information presented in this book.
Jython, Java and jHepWork -- to Jython -- Mathematical Functions -- One-dimensional Data -- Two-dimensional Data -- Multi-dimensional Data -- Arrays, Matrices and Linear Algebra -- Histograms -- Random Numbers and Statistical Samples -- Graphical Canvases -- Input and Output -- Miscellaneous Analysis Issues Using jHepWork -- Data Clustering -- Linear Regression and Curve Fitting -- Neural Networks -- Steps in Data Analysis -- Real-life Examples.
Keywords: Computer science; Data mining; Computer Science; Computer Science, general; Data Mining and Knowledge Discovery